STUDI TENTANG PERKEMBANGAN EMOSI PESERTA DIDIK SMK NEGERI 1 PONTIANAK - Mery, Mery; Asrori, Muhammad; Wicaksono, Luhur (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractThis thesis aims to find out the emotional development of students of SMK Negeri 1 Pontianak ". The method used is descriptive method with survey form. While the collection techniques used are indirect communication techniques with a questionnaire collection tool. The results of the study are as follows: 1), the anger of students shows the category of "medium". This means that they have started to control their emotions and have feelings that are not easily upset with their friends. 2). Sadness of students shows the category "medium". This means it is not easy to feel sad and not easy to feel hopeless and depressed. 3). The fear of students shows the category "medium". participants are not easily scared, and are nervous. 4). Student enjoyment shows the "high" category. Students feel happy and can enjoy life. 5). Student love shows the "high" category. Students are easy to accept others, build friendship and trust .. 6). Surprised the students showed the "high" category. Participants easily feel lonely, amazed and stunned. 7). Annoyed students show the category of "high". Learners easily feel despised, fed up and hate. 8). Embarrassed students show the category of "high". This can be interpreted that students easily feel guilty and upset.Â Keywords: Â Emotional Development Of Students